Edward Byrne Memorial Justice Assistance Grant (JAG) Program: Evaluation Report - Behm, Mike (2013)
The Consortium for Crime and Justice Research (CCJR) at the University of Nebraska – Omaha is conducting an evaluation of projects supported by Nebraska’s 2012 Edward Byrne Memorial Justice Assistance Grant (Byrne JAG) Program funds. The primary goal of the evaluation is to provide the Nebraska Commission on Law Enforcement and Criminal Justice (Crime Commission) a summary of the law enforcement, training, prevention, and associated activities occurring as a direct or indirect result of the infusion of Bryne JAG funds. In other words, the intent of the evaluation is to provide a summary of the funded activities and resulting products from Byrne JAG dollars. A subsidiary goal is to track the use of evidence-based practices (EBPs) supported by JAG funds. Because federal funding agencies continue to emphasize the use of practices that are supported by research evidence, we are tracking the use of EBPs, as well as fidelity to the model of the practices that have been adopted. This report provides an overview of activities and products of funded agencies based on required performance indicator data submitted for October to December 2012 and January to March 2013. Because the funded task forces report similar data, their feedback is included in one section. In addition to the task forces, information is provided to summarize the activities of Banister’s Leadership Academy, the Nebraska Crime Commission, The Indian Center, the Law Enforcement Training Center, the Nebraska Department of Corrections, the Douglas County Attorney’s Office, and the Nebraska Attorney General’s Office